The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1182/blood.2019000051
|View full text |Cite
|
Sign up to set email alerts
|

Increased SLAMF7high monocytes in myelofibrosis patients harboring JAK2V617F provide a therapeutic target of elotuzumab

Abstract: Monocyte-derived fibrocytes recently garnered attention because the novel pathogenesis of myelofibrosis (MF), and suppression of fibrocyte differentiation by serum amyloid P remarkably improved MF. We previously revealed that human fibrocytes highly expressed signaling lymphocytic activation molecule F7 (SLAMF7) compared with macrophages and that SLAMF7high monocytes in the peripheral blood (PB) of MF patients were significantly elevated relative to those in healthy controls (HCs). In this study, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…6b). In particular, we found that SLAMF7, a cell surface marker previously shown to play a role in fibrocyte differentiation in myelofibrosis, was upregulated in JAK2-V617F CD14+ cells 35 . Thus, this population of cells could potentially be an early biomarker for risk of progression to myelofibrosis.…”
Section: Transcriptional Differences Between Jak2-v617f and Jak2-wt Hmentioning
confidence: 67%
“…6b). In particular, we found that SLAMF7, a cell surface marker previously shown to play a role in fibrocyte differentiation in myelofibrosis, was upregulated in JAK2-V617F CD14+ cells 35 . Thus, this population of cells could potentially be an early biomarker for risk of progression to myelofibrosis.…”
Section: Transcriptional Differences Between Jak2-v617f and Jak2-wt Hmentioning
confidence: 67%
“…In the unstimulated state, SLAMF7 is expressed at high levels by plasma cells ( 35 ), and can also be expressed on B cells, T cells, and natural killer (NK) cells, but is expressed at low levels on resting macrophages ( 34 , 36 ). However, elevated SLAMF7 expression has been found on macrophages from atherosclerotic lesions ( 37 ) and from patients with myelofibrosis ( 38 ). BLIMP-1 regulates SLAMF7 expression in lymphocytes ( 39 ), but it is not well understood how this receptor is regulated in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Japanese investigators validated and extended this work to show that fibrocyte differentiation is triggered by myeloproliferative leukemia (MPL) receptor activation (by thrombopoietin) and that circulating monocytes highly expressing signaling lymphocytic activation molecule F7 (SLAMF7) were possible fibrocyte precursors [ 47 ]. They went on to show that particularly in JAK2 -mutated MF patients, the circulating SLAMF7 high monocyte percentage was significantly elevated, and correlated with JAK2 V617F allele burden [ 48 ]. While the former work from our group served as the basis for studying PRM-151 (recombinant pentraxin-2, or serum amyloid protein) in patients with MF (discussed below), the Japanese group identified the anti-SLAMF7 monoclonal antibody, elotuzumab, as a therapeutic candidate in MF.…”
Section: Targeting Bone Marrow Fibrosis In Mfmentioning
confidence: 99%
“…While the former work from our group served as the basis for studying PRM-151 (recombinant pentraxin-2, or serum amyloid protein) in patients with MF (discussed below), the Japanese group identified the anti-SLAMF7 monoclonal antibody, elotuzumab, as a therapeutic candidate in MF. Elotuzumab inhibited fibrocyte differentiation in vitro and ameliorated bone marrow fibrosis and splenomegaly induced by romiplostim (thrombopoietin agonist) administration in humanized mice [ 48 ]. Accordingly, there are plans to study this agent in patients with JAK2 -mutated MF who are not candidates for JAK inhibitor therapy (NCT04517851).…”
Section: Targeting Bone Marrow Fibrosis In Mfmentioning
confidence: 99%